Evaluation of Periarticular Soft Tissues in Patients With Juvenile Idiopathic Arthritis by Superb Microvascular Imaging and Shear Wave Elastography - Ömer Faruk ÜNAL,; Zuhal BAYRAMOĞLU,; İbrahim ADALETLİ, (Archives of Rheumatology, 2020)
Objectives: This study aims to compare the vascularity and elasticity of periarticular soft tissues by superb microvascular imaging (SMI) and power Doppler (PD) ultrasound along with shear wave elastography (SWE) between children with juvenile idiopathic arthritis (JIA) and healthy children. Patients and methods: This prospective single center study, conducted between March 2018 and May 2018, included 22 children with JIA (14 males, 8 females; mean age 11.27±5 years; range, 5 to 17 years) and 24 healthy pediatric volunteers (12 males, 12 females; mean age 13±5.5 years; range, 7 to 17 years). Quadriceps tendon (QT), patellar tendon (PT), infraarticular and supraarticular soft tissue elasticities were calculated via SWE. Supraarticular and infraarticular soft tissue vascularity index (VI) were evaluated via SMI and PD. Results: No significant difference was found among the mean ages of the participants in study and control groups. Mean VI of both supraarticular (8.15%) and infraarticular soft tissues (7.9%) by SMI were significantly higher in study group compared to control group (2.88% vs. 2.57%, respectively). Mean VI of both supraarticular (9.1%) and infraarticular soft tissues (8.12%) by PD were significantly higher in study group compared to control group (3.4% vs. 3.1%, respectively). Highly significant good positive correlation was found between VI values obtained with PD and SMI (r=0.9, p=0.001). There was a significant moderate positive correlation between the mean elasticity of the QT with VI of the supraarticular soft tissues by SMI (r=0.4, p=0.003). There was a significant moderate positive correlation of VI of infraarticular soft tissues by SMI with mean elasiticity of PT (r=0.42, p=0.002). Conclusion: Vascularity index by SMI and PD could differentiate patients with JIA from healthy subjects. The SWE examination of tendons and soft tissues did not show any significant difference among patients with JIA and healthy subjects.